Derivational Noun Suffixes Found in Dive Studios YouTube Channel Entitled “How Did I Get Here?” - I. G. B. Wahyu Nugraha Putra; Dewata, Kirana Intan (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
In this research concerns with derivational noun suffixes in the Dive Studios YouTube Channel entitled “How Did I Get Here?” episode 1. The method that used in this research descriptive quantitative method to identify the types and the progress of derivational noun suffixes that found in the data source. This research found 57 data in total that found in the data source. By using theory from Plag (2002) this theory claims there are twenty-two types of derivational noun suffixes there are -ness, -age, -al, -ship, -an, -ance, -ing, -ion, -ant, -ism, -ist, -cy/-ce, -ity, -ment, -dom, -ee, -eer, -(e)ry, -ess, -ful, -hood, -er. But in this research only found five suffixes out of twenty-two. And in this study were found five types of derivational noun suffixes: -ing, -ion, -ment, -ful, and -ist.